Effect of Therapist Coaching Statements on Parenting Skills in a Brief Parenting Intervention for Infants. Issue 4 (July 2022) - Heymann, Perrine; Heflin, Brynna H.; Bagner, Daniel M.
Behavioral parenting interventions have been shown to decrease early childhood behavior problems by improving parenting skills. Few studies have examined the impact of therapist coaching statements on parenting skill acquisition, especially among ethnic minority families and non-English-speaking families. In this study, we examined therapists' use of responsive and directive coaching statements during the first coaching session in a brief parenting intervention, the Infant Behavior Program (IBP), on changes in parenting skill acquisition. Participants were 24 mothers of 12- to 15-month-olds, with elevated levels of behavioral problems from primarily Latinx and low-income backgrounds. Mothers who heard more responsive coaching from their therapist showed greater increases in positive parenting skills. Spanish-speaking therapists used fewer responsive coaching statements and more commands, however, language spoken did not moderate the effect of these statements on changes in parenting skills. Responsive coaching statements in English and Spanish had a positive impact on parenting skill acquisition.